Initiatives of papain industry by private-public-farmer link ages in classical biocontrol program for papaya mealybug in Tamil Nadu (The Journal of Plant Protection Sciences, 2022)
Papaya cultivation for papain production is taken up by many progressive farmers in Tamil Nadu and facilitated  by Senthil Papain and Food Products Ltd (SPFP), Coimbatore since 2004. The onslaught by the new invasive mea lybug (PMB)-Paracoccus marginatus Williams and Granara de Willink) in 2006 caused major concern in papain  production. The need for repeated application of insecticides and dearth of labour for application of insecticides  made it difficult for the farmers to maintain the crop and forced many farmers to even abandon papaya crop  cultivation altogether. Considering the drastic reduction in the wet latex supply, SPFP has taken up series of initia tives which are summarized in this paper. Initially, a survey made in more than 80 farmers holdings supplying wet  latex to the industry to get the first hand information on the extent of mealy bug incidence. Secondly, it facilitated  select cluster of papaya growers to meet the concerned authorities and scientists of Tamil Nadu Agricultural Uni versity (TNAU), Coimbatore to appraise them of the gravity of the situation and the need for getting effective  biocontrol agent [Acerophagus papayae (Noyes and Schauff)] through ICAR-NBAII (National Bureau of Agri culturally Important Insects)-TNAU was emphasized as the existing biocontrol agents could not give relief. Later,  when the exotic parasitoid was imported by NBAII, Bangalore, the papain industry wholeheartedly supported the  training programmes by deploying its field staff in release and multiplication of the parasitoid. For enabling ini tial multiplication of the released parasitoids, farmers of heavily infested papaya fields were compensated for the  yield loss to serve as field-mass-multiplication-strategy. Further, the farmers of neighbouring fields were encoura ged and facilitated through thirteen field staff to take the bug infested leaves and fruits from parasite-released fields  and dispersed in new fields. The effective mass-spreading of parasitoid was made thorough door-to-door contact  and farmers were monitored not to take up spraying. The infested plant parts from infested fields were availed re gularly by TNAU to facilitate mass production of parasitoid. This is a successful model of partnership of private  sector-public institutions in biocontrol of the PMB biocontrol which has practically impacted through rise in quali ty and quantity of latex supply and area increase in papaya cultivation.
Keywords: Papaya mealybug; Acerophagus papayae; biocontrol; industry-scientists linkage